(untitled) (International Journal of Research in Pharmacology & Pharmacotherapeutics, 2021)
Current review was regarding Diabetes mellitus along with its causes for foot ulcer. Many studies were conducted regarding etiology of diabetes mellitus. This review highlights the prevalence of diabetes and its neuropathic complications leading to ulceration stage. Current review details the underlying mechanism foot ulcer and its reason. Diabetes mellitus is increasingly common conditions in low income countries that expose patients to increased risk of mortality and morbidity. There is a long preclinical period (up to 9 to 13 years) marked by the presence of immune markers when β-cell destruction is thought to occur. Hyperglycemia occurs when 80% to 90% of β- cells are destroyed. There is a transient remission followed by established disease with associated risks for complications and death. Type 2 diabetes is usually characterized by the presence of both insulin resistance and relative insulin deficiency. Insulin resistance is manifested by increased lipolysis and free fatty acid production, increased hepatic glucose production, and decreased skeletal muscle uptake of glucose. β-Cell dysfunction is progressive and contributes to worsening blood glucose control over time. Identifying participants in the pre-clinical stages by screening offers participants and providers an opportunity to modify long-term risk before serious complications occur. Early detection of diabetes can be facilitated by periodic screening of the people regularly. Counselling of the community may help in lifestyle modification and its role in controlling hypertension and diabetes along with its complications and which should also be emphasized.